2016
DOI: 10.1007/s40271-016-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Class Analysis to Identify Variation in Caregivers’ Preferences for their Child’s Attention-Deficit/Hyperactivity Disorder Treatment: Do Stated Preferences Match Current Treatment?

Abstract: Objectives To investigate variation in caregiver preferences for their child’s attention-deficit/hyperactivity disorder (ADHD) care and to determine if their stated preferences align with current care management. Methods Caregivers of a child aged 4–14 years and in care for ADHD were recruited from pediatric outpatient clinics and advocacy groups across the state of Maryland. Participants completed a survey collecting demographics, the child’s treatment, and caregiver preferences—elicited using a best-worst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Yet, it has also been shown that >40–60% of patients discontinue this treatment for several reasons (Duric et al, 2017; Garbe et al, 2012; Pappadopulos et al, 2009). Even though similar discontinuation rates have been observed in one non-pharmacological treatment study (Duric et al, 2017), these treatment approaches are steadily gaining popularity (Dosreis et al, 2017; Ng et al, 2017; Schatz et al, 2015). Amongst non-pharmacological approaches, neurofeedback (NF) has gained increasing acceptance and interest.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Yet, it has also been shown that >40–60% of patients discontinue this treatment for several reasons (Duric et al, 2017; Garbe et al, 2012; Pappadopulos et al, 2009). Even though similar discontinuation rates have been observed in one non-pharmacological treatment study (Duric et al, 2017), these treatment approaches are steadily gaining popularity (Dosreis et al, 2017; Ng et al, 2017; Schatz et al, 2015). Amongst non-pharmacological approaches, neurofeedback (NF) has gained increasing acceptance and interest.…”
Section: Introductionmentioning
confidence: 72%
“…While the neurophysiological mechanisms associated with treatment effects seem to be different between MPH and NF interventions, the behavioral results suggest that both interventions are equally effective to treat inhibitory deficits as examined using the Go/Nogo task in the current study. This is of high clinical relevance because it has been shown that a significant proportion of patients discontinue MPH treatment for several reasons and prefer non-pharmacological treatment approaches (Dosreis et al, 2017; Garbe et al, 2012; Ng et al, 2017; Schatz et al, 2015). The finding that both interventions seem to target complementary cognitive-neurophysiological processes and functional neuroanatomical structures may provide the basis for a combined MPH + NF intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to evaluate the rank-order importance in a descriptive assessment of the value elements. The research team used stated-preference methods to quantify preferences using regression models [16][17][18][19]. The resulting beta estimates, or preference weights, inform their relative importance in patient-informed value-based decisions.…”
Section: Recommendation 2: Quantifying Patient-informed Value Elementsmentioning
confidence: 99%
“…Most studies only examined a single attribute versus multiple aspects related to various stimulant preparations, and they often lacked rigorous methods for assessing preference. [15][16][17][18][19][20][21][22][23][24][25] Largely missing from these studies is the voice of the adult patient with ADHD 17 The primary aim of this study was to evaluate preferences for specific features associated with long-acting stimulant treatment among adult patients with ADHD in the US.…”
Section: Introductionmentioning
confidence: 99%